1994
DOI: 10.1177/036354659402200306
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Donor Age and Strain Rate on the Biomechanical Properties of Bone-Patellar Tendon-Bone Allografts

Abstract: Over 50% of all knee injuries involve partial or complete tear of the anterior cruciate ligament. Surgical reconstruction of this ligament using an isometrically placed bone-patellar tendon-bone autograft is the current technique of choice; however, harvest of patellar tendon as a free graft can lead to increased morbidity. To address this issue, allogenic patellar tendon grafts have been introduced as alternatives to autogenic graft material. The purpose of this study was to examine effects of age and strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 35 publications
10
121
2
1
Order By: Relevance
“…16 While the preponderance of avulsion failures may also reflect the relatively slow loading rate employed in the current investigation (500 mm/min or approximately 20%/s), 21 it is worthy to note that the ultimate tensile strength and stiffness values of the LCL and MCL are comparable to those reported in the literature for isolated tests (TABLE 1), despite considerable differences in the age of specimen donors and the loading rates employed. Thus, these findings tend to support those of previous studies, in which the properties of knee ligaments have been shown to be only weakly influenced by age 2 and were relatively insensitive to loading rates ranging from 1%/s to 100%/s. 5 Although the loading rate employed in the current study was encompassed within the wide range of elongation rates (30 to 90 000 mm/min) thought to induce traumatic loading of the human knee joint, 6 there was considerable between-specimen variability in the tensile strength of the 2 ligaments, as shown in TABLE 3.…”
supporting
confidence: 90%
“…16 While the preponderance of avulsion failures may also reflect the relatively slow loading rate employed in the current investigation (500 mm/min or approximately 20%/s), 21 it is worthy to note that the ultimate tensile strength and stiffness values of the LCL and MCL are comparable to those reported in the literature for isolated tests (TABLE 1), despite considerable differences in the age of specimen donors and the loading rates employed. Thus, these findings tend to support those of previous studies, in which the properties of knee ligaments have been shown to be only weakly influenced by age 2 and were relatively insensitive to loading rates ranging from 1%/s to 100%/s. 5 Although the loading rate employed in the current study was encompassed within the wide range of elongation rates (30 to 90 000 mm/min) thought to induce traumatic loading of the human knee joint, 6 there was considerable between-specimen variability in the tensile strength of the 2 ligaments, as shown in TABLE 3.…”
supporting
confidence: 90%
“…However, this slower speed is not expected to dramatically affect tissue forces as it has been shown previously that soft tissue samples transmit similar forces when tested at 10%/s versus 100%/s. 27 (3) Alignment of the anatomical axes with robot and load cell axes was controlled accurately but could have varied from limb to limb. This is not expected to be a major factor due to the small variance in our force data within and among specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the linear tangent moduli did not show significant differences with respect to the strain rates and confirmed the observation that the strain rate effect acts mainly in the toe region. A direct consequence of this result is that the linear tangent moduli can not be used to quantify the effect of strain rate in a soft tissue as proposed for the patellar tendon specimens [22]. The quantification of the strain rate effect should use an independent variable, as the "supplemental stress" or should use a continuum mechanics approach as proposed in a recent paper [23].…”
Section: Discussionmentioning
confidence: 99%